Attachment as a Primary Mechanism in Physician Cognition and Bias During Complex Medical Cases: A Narrative Review - Rein C (Advances in Medical Education and Practice)
Carrie Rein Department of Clinical Research and Leadership, the George Washington University School of Medicine and Health Sciences, Washington, DC, USACorrespondence: Carrie Rein, Email crein15@gwmail.gwu.eduIntroduction: In recent decades, improvements in diagnostic accuracy in medical cases have been minimal despite rapid advancements in technology. Moreover, in complex cases, diagnostic accuracy remains a significant challenge, often reflecting practices from the 18th and 19th centuries. This comprehensive narrative review explores how cognitive bias may act as a critical, yet neglected, factor contributing to the persistent diagnostic error rate.Methods: A narrative review of the literature was conducted through a search of the George Washington University library databases and Google Scholar to identify studies related to physician cognition, complex medical diagnosis, and cognitive error.Results: This review synthesizes existing literature to propose a theoretical framework explaining how cognitive error, clinician cognition, tolerance of uncertainty, and attachment theory interact to influence the formation of cognitive bias at the cost of diagnostic accuracy and efficiency.Discussion: It is not only necessary for clinicians to focus on a patient’s words, symptoms, or data to improve diagnostic accuracy, but also for clinicians to relate to others’ distress through their own attachment styles: technology’s critical blind spot. Clinicians with insecure attachment styles may struggle with metacognition, exhibit lower cognitive flexibility, have reduced tolerance for uncertainty, experience lower thresholds for cognitive load, and rely more heavily on heuristics, leading to an increased likelihood of cognitive error during complex medical cases. This theory provides a foundation for further research into how attachment influences clinician decision-making and diagnostic performance while also highlighting how medical education may reinforce these patterns.Keywords: diagnostics, unconscious bias, cognitive theory, attachment theory